Construction And Evaluation Of Multigene Mutants Of Vibrio Cholerae O139 As Vaccine Candidates - Murugaiah, Chandrika (2011)
Cholera is a major health issue, affecting millions of lives annually. In light of the recurrent outbreaks of cholera, there is a pressing need for the development of vaccines that allow rapid mass vaccination. In this study, genetically modified vaccine candidates, VCUSM21P and VCUSM22P, were designed. VCUSM21P is a prototrophic vaccine which encodes non-toxic cholera toxin A (ctxA) subunit immunogen and has accessory cholera enterotoxin (ace), zonula occludens toxin (zot) and repeats-in-toxin C/A (rtxC/A) mutations. On the other hand, VCUSM22P is ace, zot, ctxA, rtxC/A and haemagglutinin/protease (hap) mutant. Both mutants were found not to disassemble the actin of HEp2 cells.